An escalation of violence in the Caucasus, hardening in Russia - Uwe Halbach (Stiftung Wissenschaft und Politik (SWP), 2004)
The most frequent series of terrorist attacks in Russia until now, which took place between August 24 and September 1, 2004 and left 430 dead, represents a new dimension of violence. The hostage-taking of children in Beslan in North Ossetia taught several new lessons: terrorist violence has crossed a new line with regard to the 'softness' of the attack's targets, the overall instability in the North Caucasus and the possibility of a far-reaching hardening of Russia in reaction to the perceived threats. Even with the complexity of the conflict situation in Russia's Caucasian periphery and notwithstanding the expansion of terrorist violence, the unresolved problem of Chechnya remains the central factor in this context. (SWP Comments / SWP)
Keywords: 320